The Association of Digital Skills, Work-Life Balance, and Rewards on Employee Performance at MSME Pentol Rezky Samarinda - Adhe Rizky Ariyanti; Rina Masithoh Haryadi; Andi Indrawati (Poltanesa, 2025)
The digital transformation of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia underscores the need to enhance employee performance through technological competence, employee well-being, and effective motivation systems. However, inconsistent findings regarding the effects of digital skills, work-life balance, and reward highlight the need for integrated empirical analysis, particularly in culinary MSMEs. This study examines the partial and simultaneous associations between these three variables and employee performance at MSME Pentol Rezky Samarinda. This research employed a quantitative positivist approach with a correlational design. A saturated sampling technique was applied to all 49 employees at Pentol Rezky. Data were collected via Likert-based questionnaires and analyzed using multiple linear regression. Instrument validity, reliability, and classical assumption tests were conducted to ensure model accuracy and compliance with BLUE criteria. All measurement items were valid and reliable, and the regression model met normality, multicollinearity, and heteroscedasticity assumptions. The findings show that digital skills (p < 0.001), work-life balance (p = 0.015), and reward (p = 0.003) each significantly associated with employee performance. Simultaneously, the three predictors exert a strong effect (F = 28.128; p < 0.001), explaining 62.9% of the variance in performance (Adjusted R² = 0.629). The results indicate that employee performance in MSMEs is shaped by a combination of digital competence, balanced work-life conditions, and appropriate reward mechanisms. Strengthening these factors is essential for enabling small businesses to remain adaptive and competitive in the digital era.